2016
DOI: 10.1089/lap.2016.0381
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Thiol-Disulfide Homeostasis of the Body to Surgical Trauma in Laparoscopic Cholecystectomy Patients

Abstract: The decrease in plasma level of native and total thiol groups suggests impairment of the antioxidant capacity of plasma; however, the delicate balance between the different redox forms of thiols was maintained during surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
8
1
Order By: Relevance
“…In a study investigating effect of elective laparoscopic cholecystectomy and open inguinalfemoral hernia repair operation on TDH, the authors have demonstrated that during operation, NT, TT and disulfide levels were found to be decreased. Additionally, 24 hours after laparoscopic surgery, NT, TT and disulfide levels were found to be increased but not return to preoperative levels [120].…”
Section: Other Disordersmentioning
confidence: 84%
“…In a study investigating effect of elective laparoscopic cholecystectomy and open inguinalfemoral hernia repair operation on TDH, the authors have demonstrated that during operation, NT, TT and disulfide levels were found to be decreased. Additionally, 24 hours after laparoscopic surgery, NT, TT and disulfide levels were found to be increased but not return to preoperative levels [120].…”
Section: Other Disordersmentioning
confidence: 84%
“…The thiol-disulphide homeostasis situation has important responsibilities in antioxidant protection, apoptosis, signal transduction, detoxification, regulation of enzymatic activity, and cellular signalling mechanisms [20,21] . Furthermore, thiol-disulphide homeostasis is increasingly being evaluated in various medical conditions in humans, such as diabetes [22] , rheumatoid arthritis [23] , cancer [25] , multiple sclerosis [33] , hepatic disorders [24] , and surgery [34] . The plasma thiol pool is constituted by cysteine, GSH, homocysteine, and albumin.…”
Section: Discussionmentioning
confidence: 99%
“…Determination of dynamic thiol‐disulphide homeostasis allows determining entire dynamic SH groups providing a benefit from determining only glutathione (GSH) level or redox couples (such as reduced/oxidised glutathione and cysteine/cystine) individually. There is limited published data concerning the effects of thiol/disulphide homeostasis in laparoscopic cholecystectomy surgeries 9‐11 . To the best of our knowledge, there is no published study to investigate the role of thiol/disulphide homeostasis in TPS and anaesthetic methods.…”
Section: Introductionmentioning
confidence: 99%
“…There is limited published data concerning the effects of thiol/disulphide homeostasis in laparoscopic cholecystectomy surgeries. [9][10][11] To the best of our knowledge, there is no published study to investigate the role of thiol/disulphide homeostasis in TPS and anaesthetic methods. Nitric oxide (NO) as a free radical can contribute to nitrosative stress, and mediates cellular signalling pathways that regulate a plethora of physiological processes.…”
mentioning
confidence: 99%